Hierarchically porous hexagonal microsheets constructed by well-interwoven MCo2S4 (M = Ni, Fe, Zn) nanotube networks via two-step anion-exchange for high-performance asymmetric supercapacitors. (March 2018) - Wu, Juan; Shi, Xiling; Song, Weijie; Ren, Hua; Tan, Changbin; Tang, Shaochun; Meng, Xiangkang
Abstract: We report a significant advance in the design and fabrication of MCo2 S4 (M = Ni, Fe, Zn) complex hierarchical structures with well-defined morphologies by achieving novel hierarchically porous hexagonal microsheets constructed by well-interwoven nanotube networks using a controllable two-step anion-exchange technique. Uniform and smooth hexagonal sheets are initially achieved for the first anion-exchange leading to nanowire-woven hexagons, followed by transformation of each nanowire to rough MCo2 S4 nanotube via the second anion-exchange. The involved mechanism of this general top-down method allowing fine nanostructure control is clarified based on our proposed new insights into ion-induced anisotropic growth and time-dependent anion-exchange reaction kinetics. The merits of both maximized porosity and low resistance facilitate fast electron transfer/ion diffusion, thus NiCo2 S4 electrode material exhibits a higher specific capacitance of 1780 F g −1 and superior rate capability than most reported NiCo2 S4 nanostructures with different morphologies as well as excellent stability (92.4% capacity retention after 10, 000 cycles at 10 A g −1 ). Furthermore, an asymmetric solid-state supercapacitor using such NiCo2 S4 as positive and N-doped graphene film as negative electrodes achieves outstanding cycle ability (92.1% retention over 5000 cycles at 20 A g −1 ) and higher energy density of 67.2 W h kg −1 (at 900 W kg −1 ) than that of similar devices. Such MCo2 S4 electrode materials are promising for the future generation of high performance supercapacitors. Graphical abstract: A general controllable two-step anion-exchange method results in novel hierarchically porous hexagonal thin microsheets constructed by well-interwoven nanotubes (NTs), which shows higher specific capacitances and superior rate capability than most reported MCo2 S4 nanostructures with different morphologies as well as excellent cycling stability at high current densities due to the highly porous and robust NT-built network architecture as well as high conductivity, all allowing asymmetric solid-state supercapacitor with such MCo2 S4 as positive electrode to achieve much superior energy density over those reported for similar devices and outstanding cycle ability.fx1 Highlights: Novel complex hierarchical MCo2 S4 hexagons with interwoven NT networks are achieved. The involved mechanism allowing fine nanostructure control is clarified. MCo2 S4 exhibits higher specific capacitances, superior rate capability and stability. Designed asymmetric capacitor has higher energy density than similar devices.